The use of functional placental magnetic resonance imaging for assessment of the placenta after prolonged preterm rupture of the membranes in vivo: A pilot study. (21st September 2021) - Hutter, Jana; Jackson, Laurence; Ho, Alison; Avena Zampieri, Carla; Hajnal, Joseph V.; Al‐Adnani, Mudher; Nanda, Surabhi; Shennan, Andrew H.; Tribe, Rachel M.; Gibbons, Deena; Rutherford, Mary A.; Story, Lisa
Abstract: Introduction: Preterm prelabor rupture of membranes (PPROM) complicates 3% of pregnancies in the UK. Where delivery does not occur spontaneously, expectant management until 37 weeks of gestation is advocated, unless signs of maternal infection develop. However, clinical presentation of maternal infection can be a late sign and injurious fetal inflammatory responses may already have been activated. There is therefore a need for more sensitive markers to aid optimal timing of interventions. At present there is no non‐invasive test in clinical practice to assess for infection in the fetal compartment and definitive diagnosis of chorioamnionitis is by histological assessment of the placenta after delivery. This study presents comprehensive functional placental magnetic resonance imaging (MRI) quantification, already used in other organ systems, to assess for infection/inflammation, in women with and without PPROM aiming to explore its use as a biomarker for inflammation within the feto‐placental compartment in vivo. Material and methods: Placental MRI scans were performed in a cohort of 12 women (with one having two scans) with PPROM before 34 weeks of gestation (selected because of their high risk of infection), and in a control group of 87 women. Functional placental assessment was performed with magnetic resonance techniques sensitive to changes in the microstructure (diffusion) and tissue composition (relaxometry), with quantification performed both over the entire organ and in regions of interest between the basal and chorionic plate. Placental histology was analyzed after delivery where available. Results: Normative evolution of functional magnetic resonance biomarkers over gestation was studied. Cases of inflammation, as assessed by histological presence of chorioamnionitis, and umbilical cord vasculitis with or without funisitis, were associated with lower T2* (mean T2* at 30 weeks 50 ms compared with 58 ms in controls) and higher fractional anisotropy (mean at 30 weeks 0.55 compared with 0.45 in controls). These differences did not reach significance and there was substantial heterogeneity both in T2* and Apparent Diffusivitiy across the cohort. Conclusions: This first exploration of functional placental assessment in a cohort of women with PPROM demonstrates that functional placental MRI can reveal a range of placental changes associated with inflammatory processes. It is a promising tool to gain information and in the future to identify inflammation in vivo, and could therefore assist in improving optimal timing for interventions designed to prevent fetal injury. Abstract : Insights into placentas from women with prolonged preterm rupture of the membranes using functional magnetic resonance imaging.